Implementasi Manajemen Pendidikan Anak Usia Dini di TPA Mushalla Al-Muttaqin Yogyakarta Berdasarkan Setting Inklusi - Yeni Amalia Lubis (STAIN Madina Press, 2024)
Abstrak The implementation of inclusive settings in some schools needs to be implemented, so that every child with a different background gets the same opportunity to get a good education. This research aims to see the implementation of education management in the Children's Education Park (TPA) with inclusion settings and what obstacles are faced from the implementation of inclusion settings. this research is a descriptive qualitative research with data collection techniques through observation, interviews, and documentation. The subjects of this study were the head of the TPA, the Coordinator, the head of takmir and the teaching staff. The results of this study indicate that 1) the implementation of child education management in TPA Mushalla al-Muttaqin is fairly good and systematic. 2) The TPA Mushalla al-Muttaqin can be a place for children with special needs (AKB) and children with underprivileged backgrounds to continue to get a proper education. 3) the application of inclusion settings at TPA mushalla almuttaqin does not always run smoothly, there are several obstacles faced, namely, the arrangement of the children's learning space looks less conducive. Second, the lack of facilities and infrastructure owned. Third, the lack of understanding of children in understanding the concept of children with special needs makes there a little distance between other children. Keywords: Implementation, Management, Inclusion Setting, Children with Special Needs.